Budidaya Maggot Lalat BSF Sebagai Pakan Ternak, KKN-Reguler Desa Bone-Bone Universitas Muhammadiyah Enrekang (UNIMEN) - Jusran, Jusran; Sartika, Dewi; Josi, Josi; Ulhaq, Muh Zia; Ismrida, Ismrida; Sukma, Sukma; Sudarmi, Sudarmi; Rahmat, Rahmat; M, Muh Zulfikar; Nashap, Nashap; Sujianto, Sujianto; Marda, Alfian; Firman, Musda; Wahyudin, Wahyudin; Nasruddin, Muhammad Irfan; Akbar, Muh.Rafli; Elihami, Elihami (LP2M Universitas Muhammadiyah Enrekang, 2023)
Waste management in a number of areas in the country is still limited and is still a problem for the environment. One way to manage waste wisely is by using it as a medium for cultivating BSF fly maggots (black soldier flies). That's why the Regular Community Service Team at Muhammadiyah University, Enrekang, Bone-bone Village Command Post, Baraka District, Enrekang Regency is cultivating BSF fly maggots in Bone-bone village. The aim of this program is to empower Bone-bone village residents to manage organic waste by cultivating BSF fly maggots into animal feed. The implementation method is by conducting training and at the same time practicing with the local Bone-bone village community and making BSF fly cages directly. The result of this activity is that animal feed is produced in the form of BSF fly maggots and organic fertilizer in packaged form ready to be marketed. The evaluation results also show that there is positive enthusiasm from residents to carry out the same cultivation.